Soils and Human Health: Connections Between Geo-Environmental, Socio-Demographic, and Lifestyle factors and Nutrition of Tribal Women of Jharkhand, India - Rekik, Fatma; van Es, Harold M. (Frontiers in Soil Science, 2022)
A holistic view on possible determinants of human health within a poor subsistence farming community is important to addressing pressing issues surrounding hidden hunger. This survey study assesses the mineral nutrition of women in rural tribal communities of Jharkhand, India, and its possible connection with the mineral status of the soils and the staple crop rice. Associations were explored with inherent and dynamic life features namely geography; socio-demographics; and agronomic, processing and cooking practices. A total of 43 soil and rice and 35 human hair samples were collected from 43 rice fields and their associated households. All samples were analyzed for micronutrients and toxic elements, which included As, B, Ba, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Se, Sr, V and Zn. Kruskal-Wallis ANOVA tests and regularized regressions methods (ridge and lasso) were performed on qualitative parameters with respect to the soil, rice and hair mineral content. For soil data, associations existed between (i) livestock management and Mo and Cd levels in the soil, (ii) most soil micronutrients and toxic elements with districts and soil textural groups. For rice, Fe concentrations differed among rice variety types (traditional> hybrid> improved), Cu between landscape positions (midland > lowland), Mn, Ba and Pb among soil textural classes, and Cr, Ba and Pb among districts. In hair, Cd significantly differed between cooking water sources (well > other), Mn between rice cooking methods (absorption > boil and drain), and Fe, Cr and Ba between the hair-dyed groups. Linear regressions with quantitative variables such as age, household size, number of years farming, fertilization duration (as proxy for land size ownership) and hair sampling length (cm) showed that only hair Ni and Cr were significantly affected by land size ownership, and that the latter mineral is also affected by hair sampling length. Although associations were in some cases uninterpretable, they present insight into the possible challenges and confounding factors in the assessment of the soil-to-human mineral interlinkages.